IN VITRO FREE RADICAL SCAVENGING ACTIVITY AND IN VIVO ANTICATARACT POTENTIAL OF HEMIDESMUS INDICUS ROOTS IN STREPTOZOTOCIN INDUCED DIABETIC RATS - Tirumani, Prabhakar; Av, Rajashekhar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Hemidesmus indicus R. Br. (HI) (Indian sarsaparilla) is traditionally used in Indian medicine for human therapy. The present study was aimed to evaluate the antioxidant activity of HI root extracts, and its effects on delaying (or) management of cataract progression in streptozoticin (STZ) induced diabetic rats. Methods: The plant roots were extracted in different solvents, estimated total phenolic content, total flavonoid content and conducted free radical scavenging potential through 1,1-Diphenyl-2-picrylhydrazyl (DPPH), 2,2 azinobis (3-ethyl benzothiazoline-6-sulphonic acid diammonium salt (ABTS) NO, OH and reducing power assays. Further, the protective effect was evaluated in STZ induced diabetic rats through administered of ethyl acetate extract of HI (200 and 400 mg/kg body weight) orally for 8 weeks to study its effect on oxidative stress and diabetic cataract progression. Results: In primary results demonstrated that the ethyl acetate extract has been showed considerable free radical scavenging activity and significantly gain body weight, gradual decreasing blood glucose levels and delay cataract progression has been observed in HI treated rats. Furthermore, we observed significantly decreased oxidative stress markers, and restoration of the antioxidant system in HI treated rats. Lens sections from experimental animal again evidenced to conform the ameliorative effect of HI on diabetic cataract. Conclusion: This obtained result's confirmed that the protective effect of HI is attributed to the antioxidant activities of plant roots and its active principles.